ENZYMES IN POULTRY NUTRITION - F. M. Khattak; T. N. Pasha; Z. Hayat; A. Mahmud (Journal of Animal and Plant Sciences, 2006)
The biggest single expense in any system of poultry production is feed accounting for up to 70% of total production cost per bird. Poultry naturally produces enzymes to aid the digestion of feed nutrients. However, they do not have enzyme to break down fibre completely and need exogenous enzymes in feed to aid digestion. This review covers the information on enzymes and their uses in poultry nutrition. Enzymes are biological catalyst composed of amino acids with vitamins and minerals. They bring about biochemical reactions without themselves undergoing any change. The benefits of using enzymes in poultry diets include not only enhanced bird performance and feed conversion but also less environmental problems due to reduced output of excreta. In addition, this review demonstrates that enzymes are a very useful tool in the study of physiological and metabolic mechanisms. Such studies will enhance our understanding regarding the role of dietary enzymes in poultry nutrition. The information presented here serves to demonstrate the significant potential of enzymes in poultry feeds.
Keywords: Poultry nutrition; enzyme supplementation.